Augustine for the Philosophers : The Rhetor of Hippo, the Confessions, and the Continentals - Troup, Calvin L.; Troup, Calvin L., 1961- (Waco, Texas : Baylor University Press, 2014)
St. Augustine of Hippo, largely considered the greatest thinker of Christian antiquity, has long dominated theological conversations. Augustine's legacy as a theologian endures. However, Augustine's contributions to rhetoric and the philosophy of communication remain relatively uncharted. Augustine for the Philosophers recovers these contributions, revisiting Augustine's prominence in the work of continental philosophers who shaped rhetoric and the philosophy of communication in the twentieth century. Hannah Arendt, Albert Camus, Jacques Ellul, Hans-Georg Gadamer, Martin Heidegger, Edmund Husserl, Jean-Francois Lyotard, and Paul Ricoeur are paired with Augustine in significant conversations close to the center of their work. Augustine for the Philosophers dares to hold Augustine's rhetoric and philosophy in dynamic tension with his Christianity, provoking serious reconsideration of Augustine, his presence in twentieth-century continental thought, and his influence upon modern rhetoric and communication studies.--Publisher.
1. The Confessions and the continentals / Calvin L. Troup -- 2. Augustine and Heidegger on acknowledging the importance of acknowledgment and the orator's art / Michael J. Hyde -- 3. Arendt and Saint Augustine: identity otherwise than convention / Ronald C. Arnett -- 4. Lyotard's Augustine / David J. Depew -- 5. Love, and interpret what you will: a postsecular Camus-Augustine encounter / Ramsey Eric Ramsey -- 6. "A limit that resides in the word": hermeneutic appropriations of Augustine / John Arthos -- 7. Self-identity and time / Algis Mickūnas -- 8. A time to be born, a time to die: Saint Augustine's Confessions and Paul Ricoeur's Time and narrative / Andreea Deciu Ritivoi -- 9. Ellul and Augustine on rhetoric and philosophy of communication / Calvin L. Troup and Clifford G. Christians -- Epilogue / Calvin L. Troup.
Includes bibliographical references and indexes.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430 -- Influence; Saint Augustine - Bishop of Hippo; Saint Augustine - Influence on Philosophers; Saint Augustine - Contributions - Rhetoric Philosophy Communication; Philosophy, Modern